The Lipid Content in the Seeds of Brassicaceae Burnett Family - Vergun, Olena; Rakhmetov, Djamal; Fishchenko, Valentyna; Rakhmetova, Svitlana; Shymanska, Oksana; Druz, Nina; Bogatel, Ludmyla (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
The goal of this paper is to demonstrate a potential of energetic value of seeds of oil plants collected in the M.M. Gryshko National Botanical Garden of the NAS of Ukraine. In the present study lipid and caloric content of cultivars and varieties of Brassica campestris D.C., Brassica junceae (L.) Czern., Brassica napus D.C., Brassica rapa subsp. rapifera Metzger, Camelina sativa (L.) Crantz and Sinapis alba L. are described. Studing of seeds of 19 samples of investigated plants was carried out by method of extraction with petroleum ether equipped with Soxhlet extractor. Content of lipids was determined in range from 17.72% (Brassica campestris f. annua D.C., cv. Pioner) to 37.61% (Brassica napus f. annua D.C., cv.s. Yamal). Comparing of Brassica campestris plants showed that winter varieties had higher level of lipids in seeds and was in range from 28.35 to 34.48%. In the spring varieties the same parameter was in range from 17.72 to 29.00%. Identification of energetic value was made by method of combustion in the oxygen and was determined in range from 5,039.33 Kcal/kg (Brassica campestris f. annua) to 6,108.00 Kcal/kg (Brassica napus f. annua D.C., cv.s. Yamal). Content of calories in the seeds of winter varieties of Brassica campestris was from 5,530.40 to 6,045.67 Kcal/kg and in spring varieties – from 5,381.33 to 5,659.11 Kcal/kg.